"The New Millennium Minstrel Show": Blackface Elements in Seinfeld, Parks and Recreation, and Miranda Sings. Issue 3 (3rd July 2019) - Abate, Michelle Ann
Abstract: : This essay traces the presence of minstrelsy in three popular American comedy shows: Seinfeld, Parks and Recreation, and Miranda Sings . More specifically, I make a case that blackface elements form a key component to the characters of Cosmo Kramer, Tom Haverford, and Miranda.